2016
DOI: 10.1002/app.44339
|View full text |Cite
|
Sign up to set email alerts
|

Re‐elucidation of the acid‐catalyzed urea–formaldehyde reactions: A theoretical and13C‐NMR study

Abstract: The acid-catalyzed urea-formaldehyde reactions were reexamined in detail by using quantum chemistry method and 13 C-NMR determinations. Some issues in the synthesis theory that were not well understood previously have been addressed and clarified. The identified reaction mechanisms and calculated energy barriers suggest that the competitive formations of methylene and methylene ether linkages are kinetically affected by both reaction energy barriers and steric hindrance effect. The thermodynamic properties det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
4
21
1
Order By: Relevance
“…This is different from the observation in an earlier study [19] where the uron content fluctuated with the change in pH. Our previous theoretical calculations using the quantum chemistry method suggested that the uron structure should be thermodynamically as stable as chain methylene linkages [20]. However, a higher kinetic energy barrier and the requirement for 1,3-dihydroxymethylureas or trihydroxymethylureas results in their relatively lower content than methylene linkages.…”
Section: C Nmr Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…This is different from the observation in an earlier study [19] where the uron content fluctuated with the change in pH. Our previous theoretical calculations using the quantum chemistry method suggested that the uron structure should be thermodynamically as stable as chain methylene linkages [20]. However, a higher kinetic energy barrier and the requirement for 1,3-dihydroxymethylureas or trihydroxymethylureas results in their relatively lower content than methylene linkages.…”
Section: C Nmr Resultscontrasting
confidence: 88%
“…In the curing process, further condensation reactions among the branched polymers formed cross-linked network. Condensation between mono-hydroxymethylureas (MMU) or between urea and MMU mainly produced linear polymers, as found in our previous study [20]. Linear polymers or the linear part of a polymer may also participate in cross-linking reactions, but the contribution would be minor.…”
Section: C Nmr Resultsmentioning
confidence: 75%
“…Figure shows the 13 C‐NMR spectra of Resin A (polyetheramine‐formaldehyde) and Resin E (PEA‐UF). Each signal observed in the spectra was identified according to chemical shifts reported in the literature, as seen in Table .…”
Section: Resultsmentioning
confidence: 99%
“…As it can be seen from the quantitative results for sample A2 in Table 1, the total content of methylene and ether linkage carbons was up to 23.2%, indicating that the condensation reactions appeared to be much faster. As shown in Figure 4, our previous theoretical calculations predicted that the carbocation intermediate can be produced through protonation of hydroxymethyl group and the condensation reactions were highly accelerated [25]. The calculated energy barriers suggested the formation of carbocation is a rate-determining step and represents an S N 1 mechanism.…”
Section: The Dmu-formaldehyde (Dmuf) Reactionsmentioning
confidence: 86%
“…This result reflects hydroxymethylations and condensations occurred simultaneously under acidic conditions. The 13 C-NMR tracking on acid-catalyzed UF reactions indicated that a part of ether linkages formed at the initial stage converted to a methylene linkage due to the latter being thermodynamically more stable and, finally, the methylene linkages became dominant [22,25]. In this context, the DMUF condensations here are still at the initial stage, and the methylene linkage will also become dominant if the reaction is allowed for a longer time.…”
Section: The Dmu-formaldehyde (Dmuf) Reactionsmentioning
confidence: 95%